2020
DOI: 10.1111/cch.12809
|View full text |Cite
|
Sign up to set email alerts
|

Safe environments—Through the eyes of 9‐year‐old schoolchildren from a socially vulnerable area in Sweden

Abstract: Background: Children are more vulnerable than adults to environmental risks. Also, children have little control over their environment. Unlike adults, they may be both unaware of risks and unable to make choices to protect their health. Children living in especially vulnerable areas might be even more at risk due to socioeconomic factors, immigration and high crime rates. Therefore, the aim of this study was to describe the perceptions that schoolchildren from a socially vulnerable area have of safe environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Research has shown that exploring the physical environment is important for children's development of self (63), and that nature activities could benefit children's mental well-being (64). In our earlier study on children's perception of their outdoor environment in a socially vulnerable area (65), the children pointed out places where they must not go, adults having warned them about the risks. In this way the adults restricted the children's freedom to move around in the local environment.…”
Section: Discussion Of the Resultsmentioning
confidence: 97%
“…Research has shown that exploring the physical environment is important for children's development of self (63), and that nature activities could benefit children's mental well-being (64). In our earlier study on children's perception of their outdoor environment in a socially vulnerable area (65), the children pointed out places where they must not go, adults having warned them about the risks. In this way the adults restricted the children's freedom to move around in the local environment.…”
Section: Discussion Of the Resultsmentioning
confidence: 97%